Experimental Research on a New Mini-Channel Transcritical CO2 Heat Pump Gas Cooler - Jiawei Jiang; Shiqiang Liang; Xiang Xu; Buze Chen; Zhixuan Shen; Chaohong Guo; Liqi Yu; Shuo Qin (Micromachines, 2023)
This paper presents the results of an experimental study on the heat transfer and pressure drop characteristics of a novel spiral plate mini-channel gas cooler designed for use with supercritical CO2. The CO2 channel of the mini-channel spiral plate gas cooler has a circular spiral cross-section with a radius of 1 mm, while the water channel has an elliptical cross-section spiral channel with a long axis of 2.5 mm and a short axis of 1.3 mm. The results show that increasing the mass flux of CO2 can effectively enhance the overall heat transfer coefficient when the water side mass flow rate is 0.175 kg·s−1 and the CO2 side pressure is 7.9 MPa. Increasing the inlet water temperature can also improve the overall heat transfer coefficient. The overall heat transfer coefficient is higher when the gas cooler is vertically oriented compared to horizontally oriented. A Matlab program was developed to verify that the correlation based on Zhang’s method has the highest accuracy. The study found a suitable heat transfer correlation for the new spiral plate mini-channel gas cooler through experimental research, which can provide a reference for future designs.